Offshoring, job satisfaction and job insecurity - Santiago Budría; Juliette Milgram Baleix (Kiel Institute for the World Economy (IfW), 2019)
This paper investigates the effects of offshoring on individual job satisfaction and perceived risk of job loss. The authors merge microdata from the German Socio-economic Panel dataset (SOEP) with indicators of insertion in global value chains at the industry level for the period 2000-2013. They test two hypotheses. First, they investigate whether workers in industries with higher offshoring intensity report lower job satisfaction and/or are more prone to be unsecure at their jobs. Second, they test whether these effects differ among four categories of collars. Their findings indicate that offshoring is associated with lower job satisfaction. Specifically, the reference individual would need a compensation of about 0.25% of her labour income to experience a 1% increase in offshoring intensity in order to maintain her job satisfaction constant. The results are also indicative of some heterogeneity in the offshoring effect, with high skilled white-collar worker being mostly unaffected by offshoring and low skilled blue-collar workers showing the largest negative effects. Moreover, the authors find that offshoring is not significantly related with job insecurity, a result that applies to all workers' categories.
Keywords: I31; F6; 330; job satisfaction; job insecurity; offshoring; Germany